From data to action: addressing geographic inequalities in rabies burden through targeted policies - He, Lu; Tan, En-Li (Frontiers in Public Health, 2025)
ObjectiveRabies remains a preventable yet fatal zoonotic disease, disproportionately affecting low- and middle-income settings. Despite global progress in prevention and control, the extent of geographic, socioeconomic, and age-related disparities in rabies burden has not been fully quantified.MethodsUsing data from the Global Burden of Disease (GBD) Study 2021, we evaluated global, regional, national, and sociodemographic index (SDI)-specific patterns in rabies burden, focusing on age-standardized rate (ASR), including age-standardized incidence (ASIR), prevalence (ASPR), mortality (ASMR), and disability-adjusted life-year rates (ASDR). Temporal trends were quantified using the average annual percentage change (AAPC). Health inequalities were examined using the slope index of inequality (SII) and concentration index (CCI), while frontier analysis was conducted to estimate potential gains relative to socioeconomic development.ResultsIn 2021, the global ASIR of rabies was 0.129 per 100,000 population [95% uncertainty interval (UI): 0.076, 0.182 per 100,000 population], the ASMR was 0.128 per 100,000 population (95% UI: 0.075, 0.181 per 100,000 population). All global ASRs declined from 1990 to 2021, yet the absolute burden remained concentrated in low-SDI countries. Marked inequalities persisted, with ASIR, ASMR, and ASDR highest in low-SDI regions and lowest in high-SDI regions, South Asia carried the greatest absolute number of deaths and disability-adjusted life-year (DALYs) cases, whereas Eastern Sub-Saharan Africa recorded the highest ASR. At the country level, Nepal showed the highest ASR, while India contributed the largest number of cases. Health inequality analysis demonstrated that the absolute gap in ASDR between the highest- and lowest-SDI countries narrowed substantially from 1990 to 2021, but relative inequalities remained stable. Frontier analysis revealed wide substantial room for improvement even in some low-resource and high-income settings.ConclusionGlobal rabies elimination requires comprehensive efforts to reduce disparities both between and within countries, primarily by expanding access to post-exposure prophylaxis, increasing dog vaccination coverage and addressing socioeconomic inequalities.